2021
DOI: 10.36096/ijbes.v3i3.271
|View full text |Cite
|
Sign up to set email alerts
|

The influence of job insecurity and person-job fit on turnover intention mediated by job satisfaction

Abstract: This study aims to examine and analyze the influence of job insecurity and person-job fit on turnover intention mediated by job satisfaction. The population of this study are permanent and contract employees of Pamella 6 and 7 Supermarket Yogyakarta, with the number of 148 people. From a total of 148 employees from management to subordinates, 108 employees of Pamella 6 and 7 Supermarket Yogyakarta become the research sample. The data analysis used in this study is path analysis using Partial Least Square (PLS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…These results are reinforced by several previous studies conducted by Masykuroh & Muafi (2021) and Sasmiaji et al (2022), where in this study it was found that job satisfaction is able to mediate the relationship that exists between job insecurity and turnover intention. These results indicate that if an employee feels job insecurity and even a sense of dissatisfaction with his job, then this can trigger an intention to move on the employee in order to get a job that he feels is better.…”
Section: Effect Of Job Insecurity On Turnover Intention Mediated By J...supporting
confidence: 85%
“…These results are reinforced by several previous studies conducted by Masykuroh & Muafi (2021) and Sasmiaji et al (2022), where in this study it was found that job satisfaction is able to mediate the relationship that exists between job insecurity and turnover intention. These results indicate that if an employee feels job insecurity and even a sense of dissatisfaction with his job, then this can trigger an intention to move on the employee in order to get a job that he feels is better.…”
Section: Effect Of Job Insecurity On Turnover Intention Mediated By J...supporting
confidence: 85%
“…The data collection instrument in this study was distributing questionnaires online using Form, which would then be transferred again to Excel to re-examine the results of the data that had been received; this method is also employed by (Masykuroh & Muafi, 2021) (Irawanto et al, 2021) and (Rahma et al, 2021).…”
Section: Data Collection Techniquesmentioning
confidence: 99%
“…In the process of looking for new jobs, only when the match improves between the job requirements of new jobs and the employee's own needs can employees improve their job satisfaction (Masykuroh and Muafi, 2021). Knowledge-intensive employees would pay more attention to the person-job match regarding the relationship between their specialty and job demands (Gaižauskienė and Tunčikienė, 2018).…”
mentioning
confidence: 99%